Delayed graft function and acute rejection following HLA‐incompatible living donor kidney transplantation. Issue 4 (27th February 2021) - Motter, Jennifer D.; Jackson, Kyle R.; Long, Jane J.; Waldram, Madeleine M.; Orandi, Babak J.; Montgomery, Robert A.; Stegall, Mark D.; Jordan, Stanley C.; Benedetti, Enrico; Dunn, Ty B.; Ratner, Lloyd E.; Kapur, Sandip; et al.
Abstract : Incompatible living donor kidney transplant recipients (ILDKTr) have pre‐existing donor‐specific antibody (DSA) that, despite desensitization, may persist or reappear with resulting consequences, including delayed graft function (DGF) and acute rejection (AR). To quantify the risk of DGF and AR in ILDKT and downstream effects, we compared 1406 ILDKTr to 17 542 compatible LDKT recipients (CLDKTr) using a 25‐center cohort with novel SRTR linkage. We characterized DSA strength as positive Luminex, negative flow crossmatch (PLNF); positive flow, negative cytotoxic crossmatch (PFNC); or positive cytotoxic crossmatch (PCC). DGF occurred in 3.1% of CLDKT, 3.5% of PLNF, 5.7% of PFNC, and 7.6% of PCC recipients, which translated to higher DGF for PCC recipients (aOR = 1.03 1.682.72 ). However, the impact of DGF on mortality and DCGF risk was no higher for ILDKT than CLDKT ( p interaction > .1). AR developed in 8.4% of CLDKT, 18.2% of PLNF, 21.3% of PFNC, and 21.7% of PCC recipients, which translated to higher AR (aOR PLNF = 1.45 2.093.02 ; PFNC = 1.67 2.403.46 ; PCC = 1.48 2.243.37 ). Although the impact of AR on mortality was no higher for ILDKT than CLDKT ( p interaction = .1), its impact on DCGF risk was less consequential for ILDKT (aHR = 1.34 1.621.95 ) than CLDKT (aHR = 1.96 2.292.67 ) ( p interaction = .004). Providers should consider these risks during preoperative counseling, and strategies to mitigate them should be considered. Abstract : The impact of acute rejection on the risk of graft loss is less consequential for incompatible compared to compatible living donor kidney transplant recipients, while the impact of delayed graft function on mortality and graft loss is comparable.